Dynamic Characteristics and Time-History Analysis of Hydraulic Climbing Formwork for Seismic Motions - Gang Yao; Haoting Guo; Yang Yang; Chengming Xiang; Soltys Robert (Advances in Civil Engineering)
With the widespread use and increasing cycle life of climbing formwork to construct high-rise buildings in earthquake-prone areas, the risk of earthquakes during the construction period increases. Hence, it is necessary to analyze the seismic response of climbing formwork. According to actual climbing formwork in the super high-rise office building of Wanda Plaza in Kunming, China, the finite element model of the climbing formwork is established on the Ansys platform. The correctness of the model is verified by comparing the natural frequencies of the actual climbing formwork and the finite element model. The time-history analysis of the climbing formwork subjected to earthquakes of varying strong magnitudes is carried out. The maximum displacement position and maximum von Mises stress position of the climbing formwork under different working conditions are determined, and the seismic response of the climbing formwork is analyzed. It has been found that when the formwork is under construction, the maximum displacement position of the climbing formwork is at the center of the long beam of the upper platform, and the maximum von Mises stress position is the joint of the outer pole of the main platform and tripod. Under the climbing condition, the maximum displacement position of the climbing formwork is at the top of the outer pole of the upper platform, and the maximum von Mises stress position is the joint of the beam of the tripod and guide rail. The climbing formwork is partially damaged under the simulated earthquake. However, the displacement is large, and some components have reached the yield state. It is recommended to strengthen the connection between the upper platform and the guide rail and enhance the strength and rigidity of the outer pole and tripod. Climbing formwork is more sensitive to horizontal earthquakes and has minimal sensitivity to vertical earthquakes. The structure attached to the climbing formwork will reduce its sensitivity to earthquakes. The research results are of practical significance for seismic design and improvement of climbing formwork.